A separator, and a battery and an electric device comprising the same
Patent Information
- Application Number
- CN202611223409.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]目前,针对电池的能量密度较低的问题,通常采用负极材料层减薄、正极材料层增厚的方式来解决,但这会导致锂离子在负极表面成核时易因局部电场或表面缺陷形成锂枝晶,锂枝晶易与电解液发生界面副反应,消耗活性锂与电解液,导致电池的循环寿命下降
本申请提供了一种隔膜,该隔膜在基膜表面设置包含金属有机框架材料的涂层,并同时调整涂层与基膜的平均厚度比值a、隔膜的透气度b以及金属有机框架材料的平均孔体积c,通过调控三者满足关系式:0.015≤a×c/b≤6.68,来使得电池兼具高安全性和长循环寿命。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a separator and a battery and electrical device containing the separator. Background Technology
[0002] Currently, the problem of low energy density in batteries is usually addressed by thinning the negative electrode material layer and thickening the positive electrode material layer. However, this can lead to the formation of lithium dendrites when lithium ions nucleate on the negative electrode surface due to local electric fields or surface defects. Lithium dendrites are prone to interfacial side reactions with the electrolyte, consuming active lithium and electrolyte, resulting in a decrease in battery cycle life. Summary of the Invention
[0003] The purpose of this application is to overcome the shortcomings of the prior art and provide a separator and a battery and electrical device containing the separator. The separator has a coating containing a metal-organic framework material on the surface of the base film. The average thickness ratio of the coating to the base film (a), the air permeability of the separator (b), and the average pore volume of the metal-organic framework material (c) are adjusted. By controlling the three factors to satisfy the relationship: 0.015≤a×c / b≤6.68, the battery can have both high safety and long cycle life.
[0004] To achieve the above objectives, in a first aspect, this application provides a diaphragm, including a base membrane and a coating, wherein the coating is disposed on at least one side surface of the base membrane, and the coating includes a metal-organic framework material; The average thickness ratio of the coating to the base film is a; The air permeability of the diaphragm is bs / 100cc; The average pore volume of the metal-organic framework material is c cm⁻¹ 3 / kg; a, b, and c satisfy the following relationship: 0.015 ≤ a × c / b ≤ 6.68.
[0005] Secondly, this application provides a battery including the aforementioned separator.
[0006] Thirdly, this application provides an electrical device including the aforementioned battery.
[0007] The beneficial effects of this application are as follows: This application provides a separator with a coating containing a metal-organic framework material on the surface of a base membrane. The average thickness ratio a of the coating to the base membrane, the air permeability b of the separator, and the average pore volume c of the metal-organic framework material are adjusted. By controlling the three factors to satisfy the relationship: 0.015≤a×c / b≤6.68, the battery can have both high safety and long cycle life. Detailed Implementation
[0008] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0009] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0010] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0011] The present application is further illustrated below with specific embodiments: This application provides a diaphragm, including a base membrane and a coating, wherein the coating is disposed on at least one side surface of the base membrane, and the coating includes a metal-organic framework (MOF) material. The average thickness ratio of the coating to the base film is a; The air permeability of the diaphragm is bs / 100cc; The average pore volume of the metal-organic framework material is c cm⁻¹ 3 / kg; a, b, and c satisfy the following relationship: 0.015 ≤ a × c / b ≤ 6.68.
[0012] In this application's technical solution, to balance battery safety and cycle life, a coating containing a metal-organic framework (MOF) is formed on the surface of the base film. Simultaneously, the average thickness ratio 'a' of the coating to the base film, the air permeability 'b' of the separator, and the average pore volume 'c' of the MOF are adjusted to satisfy the following relationship: 0.015 ≤ a × c / b ≤ 6.68. The MOF in the separator coating provides sufficient lithium storage space for lithium ion deposition at the negative electrode and promotes uniform lithium ion deposition. The matching of the coating thickness and the average pore volume of the MOF can improve the structural stability of the coating during charge and discharge. The matching of the separator permeability can promote its absorption and retention of electrolyte and block the penetration of lithium dendrites, thus enabling the battery to have both high safety and long cycle life.
[0013] The inventors discovered that depositing a MOF-containing coating on the surface of the base film results in more uniform electrolyte wetting and better lithium deposition. This can induce uniform lithium-ion deposition, suppress lithium dendrite formation, and improve battery cycle life. By controlling the average thickness ratio 'a' of the coating to the base film, sufficient lithium storage space can be provided for lithium-ion deposition at the negative electrode, promoting uniform lithium-ion deposition, reducing lithium dendrite formation, and improving battery cycle life. However, if 'a' is too large, due to the inherent brittleness of the MOF material, an excessively thick coating will result in more internal defects (such as pores or structural defects), more concentrated stress during charging and discharging, reduced mechanical strength, and increased susceptibility to damage. When a collapse occurs, the physical barrier between the positive and negative electrodes is destroyed, allowing lithium ions to directly penetrate these defective areas, forming lithium dendrites and eventually piercing the separator, causing a short circuit between the positive and negative electrodes and reducing battery safety. Reducing the average pore volume c of the MOF can improve the mechanical strength of the coating, preventing structural collapse and improving battery safety. However, if c is too small, the lithium storage space of the MOF will be reduced, making it easier for lithium dendrites to form on the negative electrode surface, thus reducing the battery's cycle life. Further improvements can be made by increasing the separator's permeability b to prevent lithium dendrite penetration, thereby improving battery safety and avoiding the cycle life reduction problem caused by excessively small c.
[0014] In some embodiments, the diaphragm satisfies the following range: a×c / b = 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 6.68, or any two of these ranges.
[0015] More preferably, a, b, and c satisfy the relationship: a×c / b=0.0375~2.5.
[0016] As mentioned above, for the separator described in this application, the relationship between the three parameters a×c / b needs to be controlled within the range of 0.015 to 6.68. If the relationship is lower than the lower limit of 0.015, it will not provide sufficient lithium storage space, and the electrolyte wetting of the separator will be hindered, making it easy to generate lithium dendrites and reduce the cycle life of the battery. However, if the relationship is higher than the upper limit of 6.68, it will result in lower mechanical strength of the coating, making the coating prone to collapse, causing short circuits between the positive and negative electrodes, and it will also be difficult to effectively prevent lithium dendrites from penetrating the separator, thus reducing the safety of the battery. When the relationship is controlled within the specified range and further optimized to the above-mentioned preferred range, the safety performance or cycle life of the battery can reach the expected level and be further improved.
[0017] In some implementations, a = 0.005~1.67.
[0018] In some implementations, a is a range of one or any two of the following: 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.67.
[0019] More preferably, a = 0.03~0.25.
[0020] In this application, the thickness ratio of the coating to the base film in the separator affects the coating thickness. Increasing the coating thickness in the separator is more conducive to providing sufficient lithium storage space for lithium ion deposition at the negative electrode in the MOF of the coating, promoting uniform lithium ion deposition, reducing lithium dendrite formation, and improving the cycle life of the battery. At the same time, when the coating thickness in the separator is large, due to the brittleness of the MOF material itself, it is easy to increase the internal defects of the coating (such as pores or structural defects), the stress during charging and discharging is more concentrated, the mechanical strength is reduced, and it is easy to collapse. The physical barrier between the positive and negative electrodes is destroyed, and lithium ions may directly pass through these defect areas, forming lithium dendrites and eventually piercing the separator, causing a short circuit between the positive and negative electrodes, and reducing battery safety. In this application, when the average thickness ratio 'a' of the coating to the base film is preferably within the above range, it can not only provide sufficient lithium storage space for lithium ion deposition at the negative electrode and promote uniform lithium ion deposition to improve the cycle life of the battery, but also better maintain the structural stability of the coating, reduce the risk of lithium dendrites piercing the separator, and improve the safety performance of the battery.
[0021] It should be noted that, in this application, the average thickness ratio 'a' of the coating to the base film can be confirmed by, but is not limited to, the following methods: 1) Pretreatment: Discharge the battery at 0.33C to the lower limit voltage (the lower limit voltage is determined according to the specific system, where LFP, NCM, and LMFP are -2.5V; lithium nickel manganese oxide is -3.5V), disassemble the empty-charge lithium-ion battery, and obtain the separator; 2) Obtain a cross-sectional SEM of the diaphragm, measure the average thickness of the coating and the base film using a scanning electron microscope, and then calculate the ratio between the two.
[0022] In some implementations, b = 50~500.
[0023] In some implementations, b = a range of one or any two of the following: 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, and 500.
[0024] More preferably, b = 150~400.
[0025] In this application, by reducing the average pore volume of the metal-organic framework material, the structural stability of the metal-organic framework material itself can be improved, thereby increasing the mechanical strength of the coating and preventing structural collapse of the coating, thus improving the safety performance of the battery. However, as the average pore volume of the metal-organic framework material decreases, the lithium storage space of the metal-organic framework material will also decrease, and lithium dendrites are easily generated on the negative electrode surface, resulting in a decrease in the cycle life of the battery. When the permeability b of the separator in this application is preferably within the above range, it can not only effectively reduce the negative impact of the reduction of the average pore volume of the metal-organic framework material, but also better reduce the risk of lithium dendrite penetration, thereby better balancing the safety performance and cycle life of the battery.
[0026] It should be noted that, in this application, the air permeability b of the diaphragm can be confirmed by, but is not limited to, the following methods: The battery was discharged at 0.33C, disassembled, and the separator was removed and soaked in DMC solvent for 10 minutes. The separator sample was then removed. Using a separator permeability meter, in a low-humidity, normal-pressure environment, with the instrument applying a pressure of 1.21 kPa, the permeability area of 100 mL of air was measured to be 6.45 cm². 2 Time required for sample (diaphragm) preparation.
[0027] In some implementations, c = 200~2000.
[0028] In some implementations, c is a range of one or both of the following: 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, and 2000.
[0029] More preferably, c = 500~1500.
[0030] In this application, when the average pore volume c of the metal-organic framework material is preferably within the above-mentioned range, it is not only more conducive to improving the structural stability of the metal-organic framework material, thereby reducing the generation of internal defects in the coating, enhancing the mechanical strength of the coating, and reducing the risk of the coating collapsing due to stress during charging and discharging; it can also provide sufficient lithium storage space, suppress the formation of lithium dendrites on the negative electrode surface, and thus enable the battery to have both high safety and long cycle life.
[0031] It should be noted that, in this application, the average pore volume c of the metal-organic framework material can be determined by, but is not limited to, the following methods: Low-temperature gas adsorption method: At low temperatures (e.g., 77K), the adsorption / desorption isotherms of gases (N2, Ar, etc.) in MOF channels are measured, and the average pore volume is calculated using theoretical models (e.g., BET, BJH, DFT).
[0032] In some embodiments, the metal-organic framework material contains conjugated double bonds, which include at least one of phthalocyanine, hexaazanaphthalene, tetrathiofulvalene, and benzimidazole types.
[0033] Conjugated double bonds in metal-organic framework materials can better improve the conductivity of the coating. The more conjugated double bonds there are, the stronger the effect on improving the conductivity of the coating.
[0034] In some embodiments, the coating comprises a doping element, including at least one of Fe, Co, Ni, Cu, and Zn.
[0035] When transition metal elements are doped into the coating, they can work better with MOF to improve the conductivity of the coating.
[0036] In some embodiments, the mass content of the dopant element is 0.1% to 5% based on the quality of the coating.
[0037] In some embodiments, the mass content of the dopant element is within the range of any one or both of the following, based on the quality of the coating: 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, and 5%.
[0038] In this application, based on the quality of the coating, when the mass content of the doped element is preferably within the above-mentioned range, it is beneficial for metal-organic framework materials (such as bimetallic MOFs like Fe-ZIF-8) to achieve electrocatalytic conversion through active sites and to physically / chemically adsorb harmful impurities (such as HF and H2O), thereby enhancing interfacial stability and suppressing side reactions; on the other hand, it can also utilize metal ions (such as Co) 2+ Increasing the number of lithium ions migrates can improve battery capacity, cycle efficiency, and charging rate. However, when the mass content of doped elements is large, it may lead to the dissolution of transition metals. The free radicals generated will decompose the electrolyte solvent, producing gases such as CO, CO2, and H2O, increasing the internal pressure of the battery and consuming the electrolyte, leading to capacity decay and safety risks.
[0039] In some embodiments, the metal-organic framework material includes at least one of MIL-53, MIL-88B, MIL-100, MIL-101, and MIL-125.
[0040] In some embodiments, the ligands in the metal-organic framework material are selected from at least one of terephthalic acid (H2BDC), pyromellitic acid (H3BTC), fumaric acid (A), 2,6-naphthalenedicarboxylic acid (C), and 4,4'-biphenyldicarboxylic acid (D).
[0041] In some embodiments, the metal-organic framework material is selected from at least one of MIL-53(Al), MIL-88B(Fe), MIL-88B(Cr), MIL-100(Fe), MIL-100(Cr), MIL-101(Cr), and MIL-125(Ti).
[0042] In some embodiments, the average thickness of the coating is 0.1 to 5 μm.
[0043] In some embodiments, the average thickness of the coating is a range of any one or both of the following: 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, and 5 μm.
[0044] In this application, when the average thickness of the coating in the separator is preferably within the above-mentioned range, it can not only provide sufficient lithium storage space for the deposition of lithium ions on the negative electrode, promote the uniform deposition of lithium ions, reduce the formation of lithium dendrites, and improve the cycle life of the battery, but also effectively reduce the number of pores or structural defects formed in the metal-organic framework material in the coating, so as to avoid the coating from collapsing due to more concentrated stress during charging and discharging, reduce the formation of defect areas, better suppress lithium dendrites, and improve the safety performance of the battery.
[0045] In some embodiments, the average thickness of the base film is 3 to 20 μm.
[0046] In some embodiments, the average thickness of the base film is a range of any one or both of the following: 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm.
[0047] In this application, when the average thickness of the base film in the separator is preferably within the above-mentioned range, it can improve the mechanical strength of the separator to resist the puncture of lithium dendrites and reduce the risk of short circuit in the battery. On the other hand, it can also maintain a shorter ion transport path to avoid the battery's internal resistance from increasing and causing its capacity to decay rapidly, thereby improving the battery's cycle life.
[0048] In some embodiments, the coating further includes a ceramic material selected from at least one of alumina, silicon dioxide, titanium dioxide, magnesium oxide, zirconium oxide, and boehmite.
[0049] In some embodiments, the coating is a single-layer structure.
[0050] In some embodiments, the coating is a two-layer structure comprising a ceramic coating and a metal-organic framework material coating, wherein the ceramic coating is located between the base film and the metal-organic framework material coating.
[0051] In this application, a double-layer coating is constructed on the surface of the base membrane by combining a ceramic coating and a metal-organic framework material coating. While maintaining the function of the metal-organic framework material coating, the ceramic coating can be used to further enhance the puncture resistance and tensile strength of the separator, thereby improving the safety performance of the battery.
[0052] In some embodiments, the puncture resistance of the diaphragm is 200-600 gf.
[0053] In some embodiments, the puncture resistance of the diaphragm is a range of any one or both of the following: 200gf, 220gf, 240gf, 260gf, 280gf, 300gf, 320gf, 340gf, 360gf, 380gf, 400gf, 420gf, 440gf, 460gf, 480gf, 500gf, 520gf, 540gf, 560gf, 580gf, and 600gf.
[0054] In this application, when the puncture resistance of the separator is preferably within the above-mentioned range, it can not only better block lithium dendrite penetration to improve battery safety, but also effectively avoid the increase of side reactions between the electrolyte and the positive and negative electrodes to improve the cycle life of the battery.
[0055] It should be noted that, in this application, the puncture resistance of the diaphragm can be confirmed by, but is not limited to, the following methods: The battery was discharged to 0.33C, the battery was disassembled, the separator was removed and soaked in DMC solvent for 10 minutes, and the separator sample was taken out. The area of the circle fixed by the test fixture was measured using a spherical needle with a diameter of 1 mm and a tip radius of 0.5 mm under a sensor condition of 500 N.
[0056] This application provides a battery including the separator described above.
[0057] In some embodiments, the battery includes a positive electrode sheet with a compaction density of 2~2.8 g / cm³. 3 .
[0058] In some embodiments, the compaction density of the positive electrode is 2 g / cm³. 3 2.1g / cm 3 2.2g / cm 3 2.3g / cm 3 2.4g / cm 3 2.5g / cm 3 2.6g / cm 3 2.7g / cm 3 2.8g / cm 3 The range of values for any one or both of them.
[0059] In this application, when the compaction density of the positive electrode sheet is preferably within the above-mentioned range, it can not only promote the timely insertion of lithium ions extracted from the positive electrode into the negative electrode to reduce the deposition of metallic lithium on the surface of the negative electrode and thus better improve the safety performance of the battery, but also effectively suppress the side reactions between the electrolyte and the positive electrode to better improve the cycle life of the battery.
[0060] In some embodiments, the positive electrode sheet includes a positive electrode material, wherein the Dv50 of the positive electrode material is 1~10μm.
[0061] In some embodiments, the Dv50 of the positive electrode material is a range of any one or both of the following: 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, and 10 μm.
[0062] In this application, when the Dv50 of the cathode material is preferably within the above-mentioned range, on the one hand, it can avoid the lithium ion diffusion path being too long, reduce heat accumulation during charging and discharging, reduce the risk of local overheating, and improve the safety performance of the battery; on the other hand, it can also reduce side reactions with the electrolyte and improve the cycle life of the battery.
[0063] It should be noted that, in this application, the Dv50 of the cathode material can be confirmed by, but is not limited to, the following methods: (1) Discharge the battery to the lower limit voltage (2.5V) at 0.33C. Take the electrode in the empty state of the battery and soak it in dimethyl carbonate (DMC) solution at room temperature (25℃) for 4 hours. After soaking, take out the negative electrode and dry it in a vacuum environment. Use a ceramic knife to scrape off the active material powder on the surface of the electrode. (2) Using a laser particle size distribution measuring instrument (Mastersizer 3000), the particle size distribution is measured according to the particle size distribution laser diffraction method (specific steps refer to GB / T19077-2016). In the particle size distribution of the material volume reference, starting from the smallest particle size, the particle size reaches 50% of the volume accumulation to obtain Dv50.
[0064] In some embodiments, the cathode material contains a dopant element selected from at least one of Ti, V, and Al; and / or, based on the mass of the cathode material, the mass content of the dopant element is 0.15% to 0.55%.
[0065] In some embodiments, based on the mass of the cathode material, the mass content of the dopant element is a range of any one or both of the following: 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, and 0.55%.
[0066] In this application, based on the mass of the cathode material, when the mass content of the doping element is preferably within the above-mentioned range, it can not only better stabilize the crystal structure of the cathode material to reduce side reactions with the electrolyte, thereby giving the battery a long cycle life; it can also better maintain the unobstructed lithium-ion transport channel, reduce the battery's internal resistance, avoid local overheating and lithium plating, and thus improve the battery's safety performance.
[0067] In some embodiments, the positive electrode material includes a positive electrode active material and a coating layer located on at least a portion of the surface of the positive electrode active material.
[0068] In some embodiments, the coating layer is preferably a carbon coating layer.
[0069] In some embodiments, the average thickness of the coating layer is 1~10 nm.
[0070] In some embodiments, the average thickness of the coating layer is a range of any one or both of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm.
[0071] In this application, a coating layer is further optimized on the surface of the positive electrode active material. The average thickness of the coating layer is preferably within the above-mentioned range. This not only effectively prevents the electrolyte from reacting with the positive electrode active material to improve the cycle life of the battery, but also avoids a long lithium-ion transport path and low utilization of active materials, thereby better ensuring the fast charging performance of the battery.
[0072] It should be noted that, in this application, the average thickness of the coating layer on the surface of the positive electrode active material can be determined by, but is not limited to, the following methods: The battery was discharged and disassembled. The resulting positive electrode sheet was soaked in dimethyl carbonate (DMC) at 25°C for 2 hours and dried. The positive electrode active material layer was then scraped off as a sample. The powder sample was uniformly dispersed in ethanol and tested by TEM (transmission electron microscopy). The magnification was adjusted to 300KX, and three different positions were selected. The magnification was then increased to 500KX to measure the thickness of the coating layer on the outer surface of the core. The number of particles was counted as 200, and the average value was calculated to obtain the average thickness of the coating layer of the positive electrode active material.
[0073] In some embodiments, the positive electrode active material is lithium iron phosphate (LFP).
[0074] In some embodiments, the cell parameter a of the lithium iron phosphate is 9~11 Å.
[0075] In some embodiments, the cell parameter c of the lithium iron phosphate is 3~6 Å.
[0076] In some embodiments, the positive electrode active material is a ternary positive electrode material (NCM).
[0077] In some embodiments, the cell parameter a of the ternary cathode material is 1~4 Å.
[0078] In some embodiments, the cell parameter c of the ternary cathode material is 12~16 Å.
[0079] In some embodiments, the positive electrode material layer further includes a conductive agent, a binder, and a dispersant.
[0080] More preferably, the conductive agent includes at least one of carbon black, acetylene black, artificial graphite, natural graphite, carbon nanotubes, and graphene; the binder includes at least one of polytetrafluoroethylene and polyvinylidene fluoride; and the dispersant includes at least one of polyvinylpyrrolidone, polyethylene glycol, sodium carboxymethyl cellulose, and polyacrylic acid.
[0081] More preferably, in the positive electrode material layer, the mass ratio of positive electrode active material, conductive agent, binder and dispersant is (94.5~98.5):(0.5~1.5):(1.3~2.2):(0.05~2).
[0082] In some embodiments, the battery includes a positive electrode and a negative electrode; the average thickness of the positive electrode material layer in the positive electrode is T1 μm, and the average thickness of the negative electrode material layer in the negative electrode is T2 μm, wherein T1 and T2 satisfy the relationship: 1.1≤T1 / T2≤2.
[0083] In some implementations, T1 / T2 is a range of any one or both of the following: 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.
[0084] In this application, it is more beneficial to improve the energy density of the battery when T1 / T2 is preferably within the above range.
[0085] In some embodiments, the battery includes a negative electrode sheet comprising a negative electrode material having a powder resistivity of 1~100 mΩ·cm.
[0086] In some embodiments, the powder resistivity of the negative electrode material is a range of any one or both of the following: 1 mΩ·cm, 5 mΩ·cm, 10 mΩ·cm, 15 mΩ·cm, 20 mΩ·cm, 25 mΩ·cm, 30 mΩ·cm, 35 mΩ·cm, 40 mΩ·cm, 45 mΩ·cm, 50 mΩ·cm, 55 mΩ·cm, 60 mΩ·cm, 65 mΩ·cm, 70 mΩ·cm, 75 mΩ·cm, 80 mΩ·cm, 85 mΩ·cm, 90 mΩ·cm, 95 mΩ·cm, and 100 mΩ·cm.
[0087] In this application, when the resistivity of the negative electrode material powder is preferably within the above-mentioned range, it can not only better ensure that lithium ions are inserted into the negative electrode in a timely manner to reduce lithium plating and improve the safety performance of the battery, but also effectively reduce the side reactions between the negative electrode and the electrolyte, avoid the continuous rupture and regeneration of the SEI film, reduce the consumption of active lithium, and improve the cycle life of the battery.
[0088] In some embodiments, the battery includes an electrolyte; the viscosity of the electrolyte at 25°C is 1.5 to 3.7 cp.
[0089] In some embodiments, the viscosity of the electrolyte at 25°C is any one or both of the following values: 1.5cp, 1.6cp, 1.7cp, 1.8cp, 1.9cp, 2cp, 2.1cp, 2.2cp, 2.3cp, 2.4cp, 2.5cp, 2.6cp, 2.7cp, 2.8cp, 2.9cp, 3cp, 3.1cp, 3.2cp, 3.3cp, 3.4cp, 3.5cp, 3.6cp, and 3.7cp.
[0090] In this application, when the viscosity of the electrolyte at 25°C is preferably within the above-mentioned range, it can not only better suppress the side reactions between the electrolyte and the positive and negative electrodes, thereby improving the cycle life of the battery, but also facilitate lithium-ion transport, reduce internal resistance, prevent the internal temperature of the battery from rising continuously, and improve the safety performance of the battery.
[0091] In some embodiments, the electrolyte also includes additives.
[0092] In some embodiments, the additive is selected from at least one of unsaturated ester additives.
[0093] In some embodiments, the mass content of the additive is 1% to 3% based on the mass of the electrolyte.
[0094] In some embodiments, the mass content of the additive is within the range of any one or both of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, and 3%, based on the mass of the electrolyte.
[0095] In this application, when the mass content of unsaturated ester additives in the electrolyte is preferably within the above-mentioned range, it is not only more conducive to the formation of an effective SEI film to reduce the side reactions between the electrolyte and the negative electrode and improve the cycle life of the battery, but also avoids the formation of an excessively thick SEI film, which would lead to increased interfacial impedance and difficulty in lithium ion insertion into the negative electrode, thereby reducing lithium deposition on the negative electrode surface and improving the safety performance of the battery.
[0096] In some embodiments, the electrolyte comprises a solvent and a lithium salt.
[0097] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluorosulfonyl)imide.
[0098] In some embodiments, the solvent is selected from at least one of linear carbonates and cyclic carbonates.
[0099] In some embodiments, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0100] In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate.
[0101] This application provides an electrical device including the battery described above.
[0102] The present application is further illustrated below with specific embodiments, which should not be construed as limiting the scope of protection claimed in this application: In this application, the battery is prepared using the following method: (1) Preparation of positive electrode sheet: According to the mass percentage of the positive electrode material layer, 80%~98% of positive electrode active material, 0.01%~3% of conductive agent and 0.01%~5% of binder are mixed evenly, and solvent is added to obtain positive electrode slurry. The positive electrode slurry is coated on at least one surface of the positive electrode current collector, and after drying, rolling and cutting, a positive electrode sheet is obtained.
[0103] In the above-mentioned positive electrode sheet, the positive electrode active material is selected from at least one of lithium cobalt oxide, nickel-cobalt ternary materials, lithium manganese oxide, lithium iron phosphate, lithium nickel manganese oxide, or lithium manganese iron phosphate.
[0104] Among them, nickel-cobalt ternary materials satisfy the general formula: Li a Ni b Co c M1 d M2 e O f R g Wherein, 0.75≤a≤1.2, 0<b<1; 0<c<1, 0<d<1, b+c+d=1; 0≤e≤0.2, 1≤f≤2.5, 0≤g≤1, f+g≤3; M1 can be Mn and / or Al, M2 is selected from at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Si, Al, W, Sr, V, Y, Mg, Co, and Li, and its content is 100~10000ppm; R includes, but is not limited to, at least one of N, F, S, and Cl.
[0105] In the above positive electrode, the conductive agent is selected from at least one of superconducting carbon (SP), acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0106] In the above-mentioned positive electrode sheet, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorinated acrylate resin.
[0107] In the above-mentioned positive electrode sheet, the dispersant is selected from at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), polyvinylpyrrolidone (PVP) or polyethylene glycol (PEG).
[0108] In the above-mentioned positive electrode, the positive current collector can be a metal foil or a composite current collector.
[0109] Specifically, the metal foil can be aluminum or an aluminum alloy.
[0110] Specifically, the composite current collector includes an intermediate high-molecular layer and metal layers disposed on both sides of the polymer layer; wherein, the polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, its derivatives, its crosslinks or copolymers; the metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy.
[0111] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent, binder and dispersant are mixed and a solvent is added to obtain a negative electrode slurry, wherein the mass percentage of negative electrode active material: conductive agent: binder: dispersant is (90%~98%): (0~5%): (1.5%~5%): (0.3%~1.5%). The negative electrode slurry is coated on at least one surface of the negative electrode current collector, dried, rolled and cut to obtain a negative electrode sheet.
[0112] In the above-mentioned negative electrode sheet, the negative electrode active material is selected as a silicon-based negative electrode material.
[0113] Specifically, the silicon-based anode material can be selected from one or more of silicon materials, silicon oxide materials, silicon carbon materials, and silicon alloy materials.
[0114] In the aforementioned negative electrode sheet, the conductive agent is selected from one or more of the following: superconducting carbon (SP), conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0115] In the aforementioned negative electrode sheet, the binder is selected from at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and sodium carboxymethyl cellulose (CMC).
[0116] In the above-mentioned negative electrode sheet, the dispersant is selected from at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, HNBR, and PVP.
[0117] In the aforementioned negative electrode, the current collector is selected from metal foil or composite current collector.
[0118] Specifically, the metal foil can be copper or a copper alloy.
[0119] Specifically, the composite current collector includes an intermediate high-molecular layer and metal layers disposed on both sides of the polymer layer. The polymer layer comprises polymeric materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers. The metal layers are selected from at least one of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys.
[0120] (3) Electrolyte preparation: Mix different organic solvents, then dissolve the fully dried lithium salt in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L; In the above electrolyte, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP), and the concentration of lithium salt in the electrolyte is 0.8~3.2 mol / L; In the above electrolyte, the solvent is selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone, acetonitrile, dimethyl glycol ether (DME), dimethyl propylene glycol ether (PGME), and tetrahydrofuran; In the electrolyte mentioned above, the additives can be negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, additives that improve battery low-temperature performance, etc. Specifically, positive electrode film-forming additives include: anisole derivatives, polymeric monomers (such as xylene and phenylcyclohexane), and boron / nitrogen heterocyclic compounds (such as LiBOB). Negative electrode film-forming additives: vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propanesulfonate lactone (PS), vinyl sulfite (ES), vinyl sulfate (DTD), and siloxane compounds.
[0121] Specifically, the siloxane compound is selected from at least one of tetradimethylvinylsiloxysilane and tris(vinyldimethylsilyl)borate.
[0122] (4) Stack the positive electrode, the above-mentioned separator and the negative electrode in sequence so that the separator is between the positive and negative electrodes to play a role in isolation. Then, wind them to obtain the bare cell. Place the bare cell in the outer packaging shell, dry it and inject electrolyte. After vacuum sealing, standing, formation and shaping, the battery is obtained.
[0123] The outer packaging includes aluminum-plastic film, metal shell, etc.; the metal shell can be aluminum, aluminum alloy (aluminum-magnesium alloy, aluminum-manganese alloy, etc.); steel, stainless steel, nickel-plated steel, carbon steel, etc.; titanium, titanium alloy, etc. Steps (1) to (4) are not in any particular order.
[0124] Example 1 A battery, the method for preparing the battery comprising the following steps: (1) Preparation of positive electrode sheet: The positive electrode active material (LFP), conductive agent acetylene black and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 96:2:2, and a slurry is prepared by vacuum stirring. The slurry is then coated on the current collector aluminum foil, and the coating surface density is set to 450 g / m². 2 After drying, cold pressing, slitting, and roller pressing, positive electrode sheets are obtained with a compacted density of 2.5 g / cm³. 3 .
[0125] (2) Preparation of negative electrode sheet: The negative electrode active material (artificial graphite), conductive agent acetylene black, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are dispersed in water at a mass ratio of 96:1:1:2. The mixture is then vacuum stirred to prepare a slurry, which is subsequently coated on both sides of the current collector copper foil. After drying, cold pressing, and slitting, the negative electrode sheet is obtained with an areal density of 170 g / m³. 2 Compacted density 1.5 g / cm³3 .
[0126] (3) Preparation of the diaphragm: Metal-organic framework material (MOF), deionized water, dispersant (PVP), binder (SBR) and wetting agent (acetylenic glycol polyoxyethylene ether) were mixed evenly in a mass ratio of 35.0:58.3:0.4:6.0:0.4 to obtain a coating slurry; then the coating slurry was coated on both sides of the base membrane (polyethylene porous membrane, thickness of 14 μm, air permeability of 300 seconds / 100cc) (coating surface density of 1.5 g / m³). 2 The coating process involves a coating gap of 1 μm, followed by drying to obtain a diaphragm (puncture resistance of 400 gf).
[0127] The preparation method of metal-organic framework materials includes the following steps: The metal source and organic ligands were mixed and dissolved in a solvent. After thorough stirring, the mixture was transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene (PTFE). The reactor was heated to approximately 200°C and maintained at this temperature for 24 hours. After the reactor cooled naturally to room temperature, the resulting solid product was separated by centrifugation or filtration and repeatedly washed with solvents such as anhydrous ethanol and deionized water to remove unreacted ligands and impurities. Finally, the washed product was vacuum-dried at an appropriate temperature to obtain a powdered metal-organic framework material.
[0128] (4) Preparation of electrolyte: Ethyl carbonate (EC): Ethyl methyl carbonate (EMC): Ethyl acetate (EA) are mixed in a volume ratio of 5:2:3 to obtain an organic solvent. Additives 1,3-propanesulfonic acid lactone (PS, mass fraction 0.5%) and ethylene sulfate (DTD, mass fraction 0.5%) are added. Then, lithium salts LiPF6 and LiFSI are dissolved in the mixed organic solvent in a molar ratio of 4:1 to prepare an electrolyte with a lithium ion concentration of 1 mol / L.
[0129] (6) The positive electrode, separator and negative electrode are wound and assembled into a cell in sequence. The cell is placed in the outer packaging shell and hot-pressed (8MPa). After drying, the electrolyte is injected. After vacuum sealing, standing for 24 hours and formation, the battery is obtained.
[0130] The formation process is as follows: After placing the battery at a high temperature of 45°C for 24 hours, place it in a glass clamp with a clamp pressure of 0.5MPa, let it stand for 10 minutes, charge it at a rate of 0.02C for 300 minutes and stop, let it stand for 10 minutes, charge it at a rate of 0.1C for 300 minutes and stop, and repeat the cycle three times.
[0131] Example 2 A battery differs from Example 1 as follows: In step (3), the coating surface density in the preparation of the separator is 1 g / m³. 2The coating gap during the coating process is 0.5 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 33.5:55.8:0.3:10.0:0.3. The reaction temperature during the MOF synthesis process is 120℃. The size of the MOF ligand is 5 Å. The pressure for hot pressing in step (6) is 13 MPa.
[0132] Example 3 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 2 g / m³. 2 The coating gap during the coating process is 3 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 35.4:58.9:0.4:5.0:0.4. The reaction temperature during the MOF synthesis process is 220℃. The size of the MOF ligand is 20 Å. The pressure for hot pressing in step (6) is 5 MPa.
[0133] Example 4 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 0.3 g / m³. 2 The coating gap during the coating process is 0.2 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 35.8:59.7:0.4:3.8:0.4. The reaction temperature during the MOF synthesis process is 110℃. The size of the MOF ligand is 3 Å. The pressure for hot pressing in step (6) is 3 MPa.
[0134] Example 5 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 10 g / m³. 2 The coating gap during the coating process is 6 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 32.4:54.0:0.3:13.0:0.3. The reaction temperature during the MOF synthesis process is 275℃. The size of the MOF ligand is 30 Å. The pressure for hot pressing in step (6) is 15 MPa.
[0135] Example 6 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 0.5 g / m³. 2 The coating gap during the coating process is 0.3 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 35.5:59.1:0.4:4.7:0.4. The reaction temperature during the MOF synthesis process is 115℃. The size of the MOF ligand is 4 Å. The pressure for hot pressing in step (6) is 4 MPa.
[0136] Example 7 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 6 g / m³. 2 The coating gap during the coating process is 4 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 32.7:54.6:0.3:12.0:0.3. The reaction temperature during the MOF synthesis process is 250℃. The size of the MOF ligand is 25 Å. The pressure for hot pressing in step (6) is 14 MPa.
[0137] Example 8 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 15 g / m³. 2 The coating gap during the coating process is 8 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 31.3:52.1:0.3:16.0:0.3. The reaction temperature during the MOF synthesis process is 300℃. The size of the MOF ligand is 35 Å. The pressure for hot pressing in step (6) is 18 MPa.
[0138] Example 9 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 0.05 g / m². 2 The coating gap during the coating process is 0.07 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 36.8:61.4:0.4:1.0:0.4. The reaction temperature during the MOF synthesis process is 100℃. The size of the MOF ligand is 2 Å. The pressure for hot pressing in step (6) is 1 MPa.
[0139] Example 10 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 1.2 g / m³. 2 The coating gap during the coating process is 0.9 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 34.9:58.2:0.4:6.2:0.4. The reaction temperature during the MOF synthesis process is 190℃. The size of the MOF ligand is 10 Å. The pressure for hot pressing in step (6) is 8 MPa.
[0140] Example 11 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 1.6 g / m³. 2The coating gap during the coating process is 1.3 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 35.1:58.4:0.4:5.8:0.4. The reaction temperature during the MOF synthesis process is 210℃. The size of the MOF ligand is 18 Å. The pressure for hot pressing in step (6) is 7 MPa.
[0141] Comparative Example 1 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 0.03 g / m². 2 The coating gap during the coating process is 0.05 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 31.8:52.9:0.3:14.7:0.3. The reaction temperature during the MOF synthesis process is 100℃. The size of the MOF ligand is 3 Å. The pressure for hot pressing in step (6) is 16 MPa.
[0142] Comparative Example 2 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 13 g / m³. 2 The coating gap during the coating process is 7 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 32.2:53.6:0.3:13.6:0.3. The reaction temperature during the MOF synthesis process is 320℃. The size of the MOF ligand is 30 Å. The pressure for hot pressing in step (6) is 15 MPa.
[0143] Comparative Example 3 A battery differs from Example 1 as follows: the coating surface density in step (3) of the separator preparation is 0.1 g / m³. 2 The coating gap during the coating process is 0.1 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 32.4:54.0:0.3:13.0:0.3. The reaction temperature during the MOF synthesis process is 110℃. The size of the MOF ligand is 3 Å. The pressure for hot pressing in step (6) is 15 MPa.
[0144] Comparative Example 4 A battery differs from Example 1 as follows: In step (3), the coating surface density in the preparation of the separator is 3 g / m³. 2 The coating gap during the coating process is 4 μm. The mass ratio of MOF, deionized water, dispersant, binder and wetting agent in the coating slurry is 36.1:60.2:0.4:3.0:0.4. The reaction temperature during the MOF synthesis process is 270℃. The size of the MOF ligand is 28 Å. The pressure for hot pressing in step (6) is 4 MPa.
[0145] Example of effect The batteries obtained in each embodiment and comparative example were tested as follows, and the results are shown in Table 2: (1) Cycle life test method: 1) Charge the battery at a constant current rate of 0.33C to 3.65V at 25℃, and then charge it at a constant voltage rate until the current is less than 0.05C; 2) Let it stand for 10 minutes; 3) Discharge the battery at a constant current rate of 0.33C to 2.5V; 4) Let it stand for 10 minutes, and perform a cycle test according to steps 1)-4) until the battery capacity is less than 80% of the initial capacity, and record the number of cycles.
[0146] (2) Test methods for safety performance At 25°C, the battery was charged at a constant current of 0.33C to 3.65V, then switched to constant voltage charging until the current was less than 0.05C, and left to stand for 30 minutes. Then, heating wires were evenly wrapped around the surface of the battery and placed in an adiabatic accelerated calorimeter (ARC) for adiabatic thermal stability test until the battery experienced thermal runaway, at which point the test ended.
[0147] Wherein, when the battery's heating rate reaches 0.02℃ / min, the battery's temperature at this time is the self-heating temperature, denoted by t1, in ℃; when the battery's heating rate reaches 1℃ / min, the temperature at this time is the thermal runaway temperature, denoted by t2, in ℃.
[0148] Table 1 Table 2 As can be seen from Table 2, the batteries in each embodiment of this application have both high safety and long cycle life. When the battery capacity is less than 80% of the initial capacity at 25°C, the corresponding number of cycles is ≥1667 cycles, and the thermal runaway temperature of the battery is ≥101°C.
[0149] As can be seen from Examples 1 to 9, when the values of a, b, and c meet the preferred range described in this application, the battery has better safety performance and cycle life; when the value of a×c / b is in the range of 0.0375 to 2.5, the battery has better safety performance and cycle life; as can be seen from Examples 1, 10, and 11, the type of metal-organic framework material in the separator coating has little impact on the battery's safety performance and cycle life.
[0150] According to Comparative Examples 1 to 4, it can also be found that regardless of whether the values of a, b, and c are within a suitable range, when the value of a×c / b is outside the range of 0.015 to 6.68, the safety performance or cycle life of the battery is too poor, that is, it is difficult to balance the high safety and long cycle life of the battery.
[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A diaphragm, characterized in that, It includes a base film and a coating, the coating being disposed on at least one surface of the base film, the coating comprising a metal-organic framework material; The average thickness ratio of the coating to the base film is a; The air permeability of the diaphragm is bs / 100cc; The average pore volume of the metal-organic framework material is c cm⁻¹ 3 / kg; a, b, and c satisfy the following relationship: 0.015 ≤ a × c / b ≤ 6.
68.
2. The diaphragm as described in claim 1, characterized in that, 0.0375≤a×c / b≤2.
5.
3. The diaphragm as described in claim 1, characterized in that, The following conditions must be met: (1) 0.005 ≤ a ≤ 1.67; (2) 50 ≤ b ≤ 500; (3) 200 ≤ c ≤ 2000.
4. The diaphragm as described in claim 1, characterized in that, The metal-organic framework material contains conjugated double bonds, which include at least one of phthalocyanine, hexaazanaphthalene, tetrathiofulvalene, and benzimidazole.
5. The diaphragm as described in claim 1, characterized in that, The coating contains a doping element selected from at least one of Fe, Co, Ni, Cu, and Zn; And / or, based on the quality of the coating, the mass content of the dopant element is 0.1% to 5%.
6. The diaphragm as described in claim 1, characterized in that, The metal-organic framework material includes at least one of MIL-53, MIL-88B, MIL-100, MIL-101, and MIL-125.
7. The diaphragm as described in claim 6, characterized in that, The ligands in the metal-organic framework material are selected from at least one of terephthalic acid, pyromellitic acid, fumaric acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid.
8. The diaphragm as described in claim 6, characterized in that, The metal-organic framework material is selected from at least one of MIL-53(Al), MIL-88B(Fe), MIL-88B(Cr), MIL-100(Fe), MIL-100(Cr), MIL-101(Cr), and MIL-125(Ti).
9. The diaphragm as described in claim 1, characterized in that, The average thickness of the coating is 0.1~5μm; and / or the average thickness of the base film is 3~20μm.
10. The diaphragm as claimed in claim 1, characterized in that, The coating also includes a ceramic material; the ceramic material is selected from at least one of alumina, silicon dioxide, titanium dioxide, magnesium oxide, zirconium oxide, and boehmite.
11. The diaphragm as claimed in claim 10, characterized in that, The coating has a two-layer structure, including a ceramic coating and a metal-organic framework material coating, with the ceramic coating located between the base film and the metal-organic framework material coating.
12. The diaphragm as claimed in claim 1, characterized in that, The coating has a single-layer structure.
13. The diaphragm as claimed in claim 1, characterized in that, The puncture resistance of the diaphragm is 200~600gf.
14. A battery, characterized in that, Includes the diaphragm as described in any one of claims 1 to 13.
15. The battery as described in claim 14, characterized in that, Includes a positive electrode sheet, wherein the compaction density of the positive electrode sheet is 2~2.8 g / cm³. 3 .
16. The battery as claimed in claim 15, characterized in that, The positive electrode sheet includes a positive electrode material, and the Dv50 of the positive electrode material is 1~10μm.
17. The battery as claimed in claim 16, characterized in that, The cathode material contains a doping element, which is selected from at least one of Ti, V, and Al. And / or, based on the mass of the cathode material, the mass content of the dopant element is 0.15% to 0.55%.
18. The battery as claimed in claim 16, characterized in that, The positive electrode material includes a positive electrode active material and a coating layer located on at least a portion of the surface of the positive electrode active material, wherein the average thickness of the coating layer is 1~10 nm.
19. The battery as claimed in claim 18, characterized in that, The positive electrode active material is lithium iron phosphate; the cell parameter a of the lithium iron phosphate is 9~11 Å; and / or the cell parameter c of the lithium iron phosphate is 3~6 Å.
20. The battery as claimed in claim 18, characterized in that, The positive electrode active material is a ternary positive electrode material; the cell parameter a of the ternary positive electrode material is 1~4 Å; and / or, the cell parameter c of the ternary positive electrode material is 12~16 Å.
21. The battery as claimed in claim 14, characterized in that, It includes a positive electrode and a negative electrode; the average thickness of the positive electrode material layer in the positive electrode is T1 μm, and the average thickness of the negative electrode material layer in the negative electrode is T2 μm, and T1 and T2 satisfy the relationship: 1.1≤T1 / T2≤2.
22. The battery as claimed in claim 14, characterized in that, It includes a negative electrode sheet, the negative electrode sheet comprising a negative electrode material, the powder resistivity of the negative electrode material being 1~100mΩ·cm.
23. The battery as described in claim 14, characterized in that, Includes an electrolyte, wherein the viscosity of the electrolyte at 25°C is 1.5~3.7 cp.
24. The battery as claimed in claim 23, characterized in that, The electrolyte includes an additive, which is selected from at least one of unsaturated ester additives; The mass content of the additive is 1% to 3% based on the mass of the electrolyte.
25. An electrical appliance, characterized in that, Includes the battery as described in any one of claims 14 to 24.
